Peran Bidan dalam Penyediaan Layanan Kesehatan Primer di Daerah Terpencil - Anindya Azzahra; Annisa Rose Maharani; Siska Tiyas Aprilia; Siti Robi’ah; Winnie Tunggal Mutika; Rini Damayanti (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2026)
Access to quality primary healthcare remains a major challenge in remote areas due to geographical, infrastructural, and human resource limitations. In such settings, midwives serve as key frontline providers bridging critical healthcare gaps. Objective: This study aims to systematically examine the roles, contributions, and challenges of midwives in delivering primary healthcare services in remote areas. Methods: A systematic literature review was conducted, analyzing 100 scholarly articles from databases such as PubMed, Google Scholar, ScienceDirect, and others. Inclusion criteria included a focus on midwifery in remote areas and primary health service contexts. Results: Findings reveal that midwives contribute significantly to antenatal care, safe deliveries, postnatal and neonatal care, child immunization, nutrition, family planning, and community health promotion. Despite their vital role, they face significant barriers including geographic isolation, infrastructure deficits, workforce shortages, cultural resistance, and personal safety concerns. Adaptive strategies such as mobile technology use, self-funded training, and strong community-based approaches are essential for sustaining services. Conclusion: Midwives are strategic agents of change in delivering equitable primary health care in remote settings. Sustained support through policy, infrastructure, training, and protection is crucial to ensure their continued effectiveness.